Congenital Fusion of Maxilla and Mandible: A Case Report - Mehdizadeh, Mohammad; Vadiati Saberi, Bardia; Noori Bayat, Shaghayegh; Pishvaie, Mohammad-Hossein (Journal of Dental School, 2019)
Objective: Congenital fusion of jaws is a rare disorder which is observed in infants and cab ne syndromic and non-syndromic. Limited mouth opening in patients can affect the child growth and cause difficulties in feeding, swallowing and breathing. Case: A In this study, a female infant from Afghanistan, settled in Qom referred to AlZahra maternity with upper and lower fusion jaws is reported. According to clinical and laboratory examinations, infant had no other disorders except the above said disease, and her jaw fusion was non-syndromic. Conclusion: Treatment of this disease in early stages not only is easier, but also can be effective in terms of child’s growth and feeding; because in most cases TMJ ankylosis occurs due to the lack of mobility and loss of function which leads to difficulties in oral operations.